2012
DOI: 10.1371/journal.pone.0052327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Cell Substrates on the Measurement of Human Influenza Virus Neutralizing Antibodies

Abstract: Eight cell lines were systematically compared for their permissivity to primary infection, replication, and spread of seven human influenza viruses. Cell lines were of human origin (Caco-2, A549, HEp-2, and NCI-H292), monkey (Vero, LLC-MK2), mink (Mv1 Lu), and canine (MDCK). The influenza viruses included seasonal types and subtypes and a pandemic virus. The MDCK, Caco-2, and Mv1 Lu cells were subsequently compared for their capacity to report neutralization titers at day one, three and six post-infection. A g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The extent of virion maturation is one factor shown to govern how many antibodies bind the virion at a given concentration of antibody (25). In several instances, the results of neutralization assays have been shown to vary when the assays are performed on multiple cellular substrates (26)(27)(28)(29)(30)(31)(32). Interest in cell type-dependent patterns of neutralization is heightened by results of the first large-scale phase IIb clinical study of a tetravalent DENV vaccine (33).…”
mentioning
confidence: 99%
“…The extent of virion maturation is one factor shown to govern how many antibodies bind the virion at a given concentration of antibody (25). In several instances, the results of neutralization assays have been shown to vary when the assays are performed on multiple cellular substrates (26)(27)(28)(29)(30)(31)(32). Interest in cell type-dependent patterns of neutralization is heightened by results of the first large-scale phase IIb clinical study of a tetravalent DENV vaccine (33).…”
mentioning
confidence: 99%
“…89 MDCK cells may also be better suited for neutralization assays. 92 Second, MDCK cells have been shown to be the most suitable for large-scale production of influenza virus. 89,93,94 Head-to-head comparison in laboratory scale bioreactors showed that MDCK cells yielded more virus than did Vero cells.…”
Section: Mdck Cell-derived Influenza Vaccines: the Final Joust?mentioning
confidence: 99%
“…148 Cytopathic effects can be observed earlier in these cells, and titres of influenza A viruses are higher in these cells than in MDCK cells. 92,[148][149][150] However, further characterization and clinical studies would be required before they could be adopted as cell substrates for influenza vaccine production.…”
Section: Mdck Cell-derived Influenza Vaccines: the Final Joust?mentioning
confidence: 99%
See 2 more Smart Citations